UTILIZATION OF MATERNAL AND CHILD HEALTH (KIA) BOOKS IN PROVIDING STIMULATION FOR CHILD DEVELOPMENT - ita maulida; Eva Purwita; Cut Yuniwati; Anita; Yusnaini (Journal of Midwifery and Community Health (JMCH), 2025)
Background: Based on WHO data in 2017, the Neonatal Mortality Rate (NAR) reached 18/1000 live births, and the Under-five Mortality Rate (IMR) reached 39/1000 live births. IMR and IMR must be anticipated in relation to the increase in children who have developmental problems. According to Riskesdas data (2018), the total development index of children aged 36-59 months in Indonesia is 88.3%. The lowest development index is literacy, at 64.6%, followed by social-emotional (69.9%), learning (95.2%), and physical (97.8%). The MCH book is one of the instruments that can be used to stimulate child development. Objective: To conduct a review of several literatures related to the influence of the use of KIA books in providing stimulation for child development. Method: This study uses a literature review that examines the concepts and theories related to the use of MCH books in stimulating child development. The number of articles reviewed is four. Results: The MCH book can be used as one of the instruments to stimulate toddler development. After receiving health education through the MCH book, there was an increase in mothers' knowledge about stimulating child development. Conclusion: The MCH book is one of the tools that mothers can use to stimulate child development, enabling them to detect early signs of stunted child development and treat it promptly to overcome growth and development issues.